2015
DOI: 10.1038/ncomms9293
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Corrigendum: GABA signalling modulates plant growth by directly regulating the activity of plant-specific anion transporters

Abstract: The original version of this Article contained a typographical error in the spelling of the author Matthew Gilliham, which was incorrectly given as Matthew Gillham. This has now been corrected in both the PDF and HTML versions of the Article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…organisms is amplified during early development by a system of gap junctions and ion channel-driven bioelectrical cues into animalwide axial patterning (the appearance of a new anatomical level -"whole body symmetry") (Levin, 2003(Levin, , 2006. The developmental control bioelectric network shares mechanistic evolutionary history with the nervous system, and the conservation extends not only to mechanisms of targeting connections [such as neural-like mechanisms deployed in plant pollen tubes (Palanivelu and Preuss, 2000)] but to the ubiquitous use of neurotransmitter molecules downstream of bioelectric driving forces [e.g., GABA and the serotonin-like Auxin used in many plants (Ramesh et al, 2015)]. An intermediate form (Prindle et al, 2015;Humphries et al, 2017;Lee et al, 2017;Liu et al, 2017).…”
Section: A B Cmentioning
confidence: 99%
“…organisms is amplified during early development by a system of gap junctions and ion channel-driven bioelectrical cues into animalwide axial patterning (the appearance of a new anatomical level -"whole body symmetry") (Levin, 2003(Levin, , 2006. The developmental control bioelectric network shares mechanistic evolutionary history with the nervous system, and the conservation extends not only to mechanisms of targeting connections [such as neural-like mechanisms deployed in plant pollen tubes (Palanivelu and Preuss, 2000)] but to the ubiquitous use of neurotransmitter molecules downstream of bioelectric driving forces [e.g., GABA and the serotonin-like Auxin used in many plants (Ramesh et al, 2015)]. An intermediate form (Prindle et al, 2015;Humphries et al, 2017;Lee et al, 2017;Liu et al, 2017).…”
Section: A B Cmentioning
confidence: 99%
“…Stomatal aperture plays a key role in plant drought tolerance [ 77 , 149 , 150 ]. Stomatal guard cells contain a large amount of ALMT protein [ 151 , 152 ], which is the key factor in stomatal movement. In 2021, Xu et al [ 153 ] showed that ALMT9 is the key GABA signal that regulates plant cells.…”
Section: Function and Mechanism Of Gaba In The Regulation Of The Abio...mentioning
confidence: 99%
“…Several years ago, a putative GABA receptor – ALMT1 – was identified in plants ( Ramesh et al, 2015 ). This receptor belongs to the anion channel aluminium-activated malate transporter (ALMT) family (for a review of the ALMT family, see Sharma et al, 2016 ).…”
Section: Gabamentioning
confidence: 99%
“…ALMTs are not homo8logues of the animal GABA receptor. The only homology between animal GABA A ion-channel receptors and ALMT resides in a 12 amino acid motif ( Ramesh et al, 2015 ). A homologue of this peptide is found in most ALMT proteins ( Ramesh et al, 2016 ).…”
Section: Gabamentioning
confidence: 99%
See 1 more Smart Citation